1970
DOI: 10.1021/ac60294a013
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometric studies of multicomponent activity coefficients using the lanthanum fluoride membrane electrode

Abstract: The hydrogen chloride-time curve obtained in the chloridization of a typical oxide ore (reaction 2) from the Zambian Copperbelt is given by curve A of Figure 3. Curve B shows the hydrogen chloride feed to the reactor as controlled by a flow controller and a mass flow meter. Again, the hydrogen chloride partial pressure-time behavior can be readily determined from the curve. The data show that initially the rate of hydrogen chloride consumption is high, the rate then tapering off as the extent of reaction incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1972
1972
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…In this case there is not only a 10-fold improvement in precision but also a dramatic change in the ^(NaF) value. Insofar as comparison is possible, the result is again in agreement with literature values (40,41).…”
Section: Table II Liquid Junction Potentials Atsupporting
confidence: 91%
“…In this case there is not only a 10-fold improvement in precision but also a dramatic change in the ^(NaF) value. Insofar as comparison is possible, the result is again in agreement with literature values (40,41).…”
Section: Table II Liquid Junction Potentials Atsupporting
confidence: 91%
“…(8), we get that˛B < 0 in all cases (except for NaCl + NaClO 4 + H 2 O system where˛B → 0), which implies that log B > log 0 B , that is |log B | < |log 0 B |. In short and following the argument between Buttler and Huston [37] for the NaCl + NaF + H 2 O system, we can state that, generally speaking, Na + -X − interactions (being X: BF 4 , ClO 4 or NO 3 ) are slightly stronger than Na + -Cl − interactions. This behaviour will be argued later.…”
Section: Discussionmentioning
confidence: 83%
“…The following expression may then be derived [1][2][3]15,18,37]: Table 3 shows the values for˛B, as well as the sum of˛A +˛B, which should be practically constant ifˇA =ˇB =0. As can be observed, only if we consider the values for I > 1.0 mol kg −1 , results A +˛B ∼ = constant.…”
Section: Discussionmentioning
confidence: 99%
“…where β (0) , β (1) , and C γ are ion-interaction parameters, and are usually acquired by optimizing the experimental activity coefficient data using an iteration minimization procedure (e.g., Butler and Huston, 1970). For 1:1 electrolytes, many authors Gupta, 1979;Hernández-Luis, 2003;Kozlowski et al, 1987;Pitzer, 1973;Wang et al, 1994) have observed that β (0) (usually identified with the total binary ionic interactions) and β (1) (identified with interactions between unlike-charged ions) varied linearly as a function of the inverse solvent dielectric constant in water and mixed solvents.…”
Section: Downloaded By [Northeastern University] At 07:36 27 Novembermentioning
confidence: 99%